2000
DOI: 10.2114/jpa.19.207
|View full text |Cite
|
Sign up to set email alerts
|

The Turnover of Body Water as an Indicator of Health.

Abstract: Water homeostasis is essential for healthy living. Body water turnover, meaning the replacement of body water that is lost in a given period of time, has been examined in a number of previous studies, and a review of their results has yielded the following findings. Children up to 15 years of age show higher body water turnover than adults, although it is not clear how the aging process influences body water. Among people of similar age, the rate of body water turnover seems to be higher in those who exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Water is the largest constituent in the human body (1). Total body water (TBW) constitutes ∼55% body weight in adolescents (2) and can vary depending on age, sex, and percentage body fat (3). Water turnover is defined as the input and output of water over a given period of time (4) and reflects body water homeostasis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Water is the largest constituent in the human body (1). Total body water (TBW) constitutes ∼55% body weight in adolescents (2) and can vary depending on age, sex, and percentage body fat (3). Water turnover is defined as the input and output of water over a given period of time (4) and reflects body water homeostasis (3).…”
Section: Introductionmentioning
confidence: 99%
“…The DNSIYC cohort are younger than the NDNS cohort and it has been reported that water turnover is affected by age in children. 29 However, our own data in adults (unreported NDNS Y1 and 3 30 ) show that water turnover increases with age from about 20 years to 50 years of age, and so we would expect that the NDNS cohort would have greater water turnover if it was not for the fact that the DNSIYC cohort were breast-feeding. Levels of breast-feeding varied considerably from almost none to exclusively breast-feeding, as the average age of the infants was 11 months.…”
Section: Limitations and Future Workmentioning
confidence: 92%
“…The half-life of body water in humans is 7-10 days (Shimamoto & Komiya, 2000) and subjects can take sips of heavy water every day as outpatients for periods as long as several months (Messmer et al, 2005;Price, Holmes, et al, 2012;Shankaran et al, 2014). Labeling does not need intravenous administration or medical supervision, which allows measurements to be performed under free-living, ambulatory real-life conditions.…”
Section: Advantages Of the Combinatorial Analysis (Mida) Approach Formentioning
confidence: 99%